OCCURRENCE OF EGGS OF STOLEPHORUS BATAVIENSIS IN THE FISHING GROUNDS OFF MADRAS - Girijavallabhan, K G; Gnanamuthu, J C (Indian Journal of Fisheries, 2011)
The pelagic egg of Stolephorus bataviensis is described. The egg is ellipticalin shape, with a knob at one end